2004
DOI: 10.1061/(asce)0887-3828(2004)18:3(173)
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Seismic Vulnerability of Masonry Housing Types Used in Chile

Abstract: Masonry is the most used construction material, especially for residential dwellings built in all regions of Chile, up to four stories high. The masonry wall's reinforcement of these buildings can be classified into three types: confined, reinforced and hybrid. Although buildings with confined masonry walls have limited shear strength and ductility, they have demonstrated acceptable seismic behavior. Experience for buildings with the other two types of reinforcement has been different; during the 1985 Llolleo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 1 publication
0
17
0
2
Order By: Relevance
“…A few adobe houses were completely destroyed, many adobe and simple masonry buildings suffered significant damage (Figure 6 a). Also few masonry buildings with steel frame show moderate to substantial damage, an expected behavior (Moroni et al 2004). Two overpasses on the highway fully and another two showing minor structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…A few adobe houses were completely destroyed, many adobe and simple masonry buildings suffered significant damage (Figure 6 a). Also few masonry buildings with steel frame show moderate to substantial damage, an expected behavior (Moroni et al 2004). Two overpasses on the highway fully and another two showing minor structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…CM structure has been subjected to many devastating earthquakes. Table 1 includes some countries where CM buildings have been used for housing construction and the history of remarkable earthquake experienced by them [5][6][7][8][9][10][11][12][13][14][15][16][17]. As mentioned in the past literature, the overall performance of the CM building in these earthquakes was very satisfactory.…”
Section: Past Seismic Performancementioning
confidence: 99%
“…The authors have found it challenging to make a distinction between the damage grades 1 and 2 (DG1 and DG2) as defined by the EMS-98 scale. It is suggested to combine these two damage grades, in a manner similar to a Chilean damage classification (Moroni et al 2004).…”
Section: Damage Classificationmentioning
confidence: 99%